Stability nature of ohmic discharges with hollow current profiles on the HL-2A tokamak. (28th September 2020) - Shen, Yong; Dong, Jiaqi; He, Hongda; Shi, Zhongbing; Li, Jia; Han, Mingkun; Li, Jiquan; Sun, Aiping; Pan, Li
Abstract: The equilibrium configurations with hollow current density profiles can effectively improve plasma confinement. The stability of the ohmic discharges with hollow current density profiles on the HL-2A tokamak was studied for various parameters, such as plasma poloidal beta β p, the axial and edge safety factors q 0 and q s, as well as the minimum safety factor q m i n . The results suggest that the restriction to the parameters of discharges with hollow current density profiles is stricter than that of conventional discharges with peaked current density profiles. In the case of q profile with reverse shear, the instability of the configuration is significantly improved with higher β p . As a result, the configuration with a hollow toroidal current profile is stable for high β p operations. Only if q 0, q s and q m i n satisfy the specific limitations, i.e. on HL-2A, only if both q 0 ≳ 2.1 and q s ≳ 3 hold, together with q s − q 0 ≳ 0.7 and q 0 − q m i n ≳ 0.7, may the configurations with the reverse shears be stable for hollow-current-type Ohmic discharge. The results may give hints for the role of the discharges with hollow toroidal current densities in the coming advanced tokamak operations.